Assessment of Hand Grip and Pinch Strengths in Children with Autism Spectrum Disorders: A Cross-Sectional Study - Olfat Ibrahim Ali; Hassan Izzeddin Sarsak; Malak Mohammed Tarshi; Manar Marji; Shmookh Turki Aljohani; Maryam Nayef Badawood; Mawda Mohammed Bamusallam; Khawla Alharbi; Zizi M. Ibrahim; Bodor Bin Sheeha; Wafaa Mahmoud Amin (Children)
Background/objective: Children with autism spectrum disorders (ASD) are recognized to experience challenges with muscle function. However, there is a lack of knowledge about muscle and hand grip strength in autism. Therefore, the study aims to assess the handgrip and pinch strength of ASD and typical children. Material and method: This study enrolled 45 participants of both sexes, 27 males and 18 females, aged 6–12 years old; 24 (13 females and 11 males) were typically developing children and 21 (5 females and 16 males) had ASD. The outcome measures were hand grip and pinch strength, with the handheld dynamometer assessing handgrip strength and the hydraulic pinch gauge evaluating pinch grip. The hydraulic pinch gauge measured the pinch strengths of the key, tripod, and pulp grips. Both groups were assessed on both their dominant and non-dominant sides. Result: A comparison of the ASD group with the control group revealed that children with ASD exhibited lower values of the hand grip, key pinch, tripod pinch, and pulp pinch strengths for both hands (p < 0.05). Conclusions: The hand and pinch strengths of ASD children are lower than those of typically developing children. Therefore, the evaluation process for children with ASD should include hand and pinch strengths as a standard component. Furthermore, the rehabilitation program for ASD should prioritize enhancing hand strength.